O papel da modulação autonômica nos ajustes de temperatura em teiús (Salvator merianae) - Scalione, Simone Serrano [UNIFESP] (2015)
There is evidence that in reptiles there is the ability to regulate the rate of heat exchange between the body and the means adjusting the peripheral blood flow and for this by increasing or decreasing the heart rate. This phenomenon causes the same body temperature is related to different heart rates if the animal is warming up or cooling down, this phenomenon is called hysteresis heart. We suggest that autonomic tone would be different for cardiac control over development and the SNA fulfill a key role in cardiovascular control that allows changes in the dynamics of heating and cooling in lizards. The objectives of this study are: 1) to compare the differences in cardiac control by the autonomic tone in different life stages of the lizards; 2) assess seasonal differences in autonomic tone in lizards and their role in thermal exchanges were used for this study lizards (Salvator merianae) from the scientific breeding, UNESP Rio Claro, SP. In the first stage of this work, we we assess the cholinergic and adrenergic tone through pharmacological blockade with atropine and propranolol, at different stages of life from Tegu (embryo, young, adults activity and dormancy) at baseline, kept at 30 ° C. In the second step we evaluated the SNA role in heating and cooling dynamics in adult lizards in activity and dormancy period, it was held cholinergic and adrenergic pharmacological blockade with atropine and propranolol. Body temperature (Tb) and heart rate (fH) were recorded by a telemetry device. In the first stage of the experiment during the embryonic stage, the adrenergic tone is the main modulator of heart rate. The transition to the control of cholinergic tone occurs in young being kept in adults, with marked elevation of cholinergic tone in tegu into dormancy. In the second stage, the autonomic blocks have not eliminated the heart hysteresis observed in lizards but the heating and cooling time varied between treatments and the seasonal period. We conclude that autonomic tone in lizards are different at each stage of development and despite the autonomic control not be primarily responsible for the cardiac hysteresis, it plays a role in thermoregulation.